Expression profiles of aquaporin homologues and petal movement during petal development in Tulipagesneriana. Issue 3 (20th November 2012) - Azad, Abul Kalam; Hanawa, Ryosuke; Ishikawa, Takahiro; Sawa, Yoshihiro; Shibata, Hitoshi
<x xml:space="preserve">Abstract</x> Previously, we have characterized two tonoplast intrinsic proteins (TIPs) and four plasma membrane intrinsic proteins (PIPs) from the 2‐day‐old petals of tulip (Tulipa gesneriana). In this study, we analyzed the development of tulip petals and stems, temperature‐dependent petal movement, the amount of 3H2O transported into petals and stems during petal movement, and the transcript levels of two TIP (TgTIP1;1 and TgTIP1;2) and four TgPIP genes in petals and stems, from the first day of petal opening to day 12. The development of the petals and stems was completed by days 6 and 9, respectively, after the first day of petal opening. Temperature‐dependent petal movement and the amount of 3H2O that was transported into petals could be detected at significant levels up to day 6 with petal movement reaching a peak at day 3. Real‐time reverse transcription‐polymerase chain reaction analysis revealed that TgTIP1;1 and TgTIP1;2 were expressed ubiquitously in petals, stems, leaves, bulbs and roots. However, the expression level of TgTIP1;2 was very low in bulbs. The expression of both TgTIP1 genes was upregulated in close association with the development of petals but not with that of the stem. The four TgPIP genes were expressed at almost the same level during the development of the petals and the stem. However, the levels of the TgTIP1 and TgPIP transcripts in petals decreased during the course of petal wilting from day 9 onwards. These results suggest that TgTIP1;1 and TgTIP1;2 may contribute to petal development.